THE USES OF POLITENESS IN PRIDE AND PREJUDICE MOVIE - Yunus, Faradiba Islamia; Mustikawati, Yunitari (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
Pride and Prejudice is a movie adaptation of the novel of the same name, Pride and Prejudice. Pride and Prejudice is a film that tells about Elizabeth's family and Elizabeth's love story with Tuan Darcy. Elizabeth was born into a fairly simple family, she has sisters named Jane, Lydia and Marry. Elizabeth's mother, Mrs. Bennet, wanted her daughter to marry a man from a wealthy family. Until one day Elizabeth met Mr. Darcy who came from a wealthy and respected family, fell in love with each other, but at the beginning of their love story they experienced many obstacles, but strong proof of their love brought them back together. This study aims to describe how Politeness can be used in everyday life and explore the types of politeness used by each character in the film Pride and Prejudice. The researcher uses a type of qualitative research method, namely by watching Pride and Prejudice films through the website. The results of this study are, there are four types of politeness request strategies used by Pride and Prejudice film characters, the four strategies are Bald on Record, Positive Politeness, Negative Politeness and Off Record. As well as what types of Politeness are often used in everyday life, namely there are two Positive Politeness and Bald on Record. One must know how to make polite requests in English, because requests can threaten both the speaker's and listener's faces. Speakers should minimize coercion in their requests. Therefore, language users must pay attention to the use of politeness strategies, especially in conveying requests so as to minimize the potential for losing face.